Is lodging research suffering from methods bias? An assessment of published research during 1990-2016. (15th June 2021) - Ali, Faizan; Koseoglu, Mehmet Ali; Okumus, Fevzi; Putra, Eka Diraksa; Yildiz, Mehmet; Dogan, Ismail Cagri
Abstract : Purpose: The study aims to investigate if lodging research suffers from a method bias by comprehensively reviewing the research methodology used in lodging related research articles. Design/methodology/approach: In all, 2, 647 published papers in 16 leading hospitality and tourism published between 1990 and 2016 are analyzed using bibliometric technique. Findings: In all, 69% of the empirical studies in lodging research across 26 years period used quantitative methods, with an increasing reliance on regression-based analysis and structural equation modeling, a disturbing plunging trend in methods diversity. Findings also suggest an increasing trend of using secondary data. Research limitations/implications: Based on the findings of this study, theoretical and practical implications for hospitality and tourism researchers are provided. Originality/value: This is the first study that reviewed a large corpus of published research (2, 647 papers in 16 hospitality and tourism journals from the last 27 years) to highlight (a) methodology used, (b) methods employed and (c) data collection and analysis procedures. Abstract : 论酒店管理研究是否遭受方法论偏见？审阅1990-2016年发表的研究作品 研究目的: 本论文旨在通过全面审阅酒店管理相关科研文章的方法论内容，来审视是否酒店管理研究遭受方法论偏见。 研究设计/方法/途径: 本论文采用文献计量分析法，样本数据为2647篇发表在1990年-2016年间酒店旅游期刊的文章。 研究结果: 近26年间发表的酒店管理研究文章的69%使用定量分析法，往往采用回归分析和结构方程模型法，大大降低了方法多样性。研究结果还表明越来越多的文章采用二手数据分析。 研究理论限制/启示: 根据本论文研究结果，酒店旅游研究学者们得到理论和实践的启示。 研究原创性/价值: 本论文是首篇审阅16个酒店旅游期刊发表的2647篇文章，以强调(a)方法论(b)研究方法以及(c)数据收集和分析过程。